2012
DOI: 10.2139/ssrn.2114592
|View full text |Cite
|
Sign up to set email alerts
|

Muslims in France: Identifying a Discriminatory Equilibrium

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 40 publications
(37 reference statements)
1
28
1
Order By: Relevance
“…The idea that immigrants may respond to such behavior by investing less in assimilation and retreating into their own ethnic enclaves has found some empirical support. Adida, Laitin, and Valfort (2014) identify a "discriminatory equilibrium" in France, whereby Muslims react to discrimination with alienation and mistrust toward natives. Schildkraut (2005) documents a correlation between Latinos' perceptions of discrimination and low political participation.…”
Section: Discrimination and Assimilationmentioning
confidence: 99%
“…The idea that immigrants may respond to such behavior by investing less in assimilation and retreating into their own ethnic enclaves has found some empirical support. Adida, Laitin, and Valfort (2014) identify a "discriminatory equilibrium" in France, whereby Muslims react to discrimination with alienation and mistrust toward natives. Schildkraut (2005) documents a correlation between Latinos' perceptions of discrimination and low political participation.…”
Section: Discrimination and Assimilationmentioning
confidence: 99%
“…Studies, for example, have shown that a significant number of Europeans believe that Muslim immigrants might take their jobs or bring insecurity to their countries (Abdelkader ). Today significant numbers of non‐Muslims, including citizens and government officials, think that European Muslims are terrorists; many European Muslims, in return, have lost their faith and trust in European governments (Adida, Laitin and Valfort ; Fekete ). A recent meta‐analysis suggests that mutual threat perception drives both anti‐Muslim and anti‐Western hostility in Europe and the United States (Obaidi et al ).…”
Section: Historical Background and Theoretical Frameworkmentioning
confidence: 99%
“…4 As a consequence, it may lower hiring and wage discrimination. On the one hand, following Becker's (1957) model of taste-based discrimination, employers as well as their employees and customers may have less distaste for interacting with well-integrated migrants compared with their less integrated counterparts (Adida et al, 2014;Handy and Greenspan, 2009). On the other hand, following Arrow's (1973) model of statistical discrimination, the volunteering signal may weaken stereotypes with respect to foreign job candidates' productivity, values and motivation (Baert and De Pauw, 2014;Derous et al, 2009).…”
Section: Introductionmentioning
confidence: 99%